EVALUASI EFEKTIVITAS, KONTRIBUSI DAN POTENSI PENERIMAAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA UTARA - Christian, Pongtuluran Andri; Sondakh, Jullie J.; Budiarso, Novi (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Regional development needs to be run or developed as an important effort to realize broad, real and responsible autonomy. Officially, Regional Autonomy is effective in Indonesia since January 1, 2001, so that regions are required to seek alternative sources of revenue that can be used to finance regional expenditures or expenditures. Since the enactment of Regional Autonomy, local governments are granted the right, authority and obligation to manage and manage their own affairs government and local communities within the system of the Unitary State of the Republic of Indonesia. Implementation of broad autonomy, real and responsible required the ability of regions to explore their own financial resources supported by the financial balance between the Central Government and Local Government.This study aims to determine the evaluation of the effectiveness, contribution and potential tax revenues to revenue native regency north minahasa. Data analysis used qualitative descriptive data. The results of this study the authors found that the effectiveness of income changed so as to the contribution and potential of hotel tax revenues. Based on this research, it can be concluded that the company needs to increase the effectiveness of contribution and the potential of tax revenue to increase local revenue. That way the authors can provide suggestions that the government continues to improve its performance so that the professionalism of work continues to improve and the level of effectiveness that has been good to continue to consistently increase.Keywords: evektifitas, contribution, potential tax revenue, local revenue